WATER MANAGEMENT IN HOSPITALITY SECTOR: A LITERATURE INVESTIGATION - Meurer, Sara (2020)
Being tourism one of the industries highly dependent on water, it is a necessary resource to ensure the hospitality sector sustainability. Due to this, the research objective is to raise the benefits coming from the international scientific literature to contribute to water resources management in the sector. To achieve this, the present research uses the intervention instrument Knowledge Development Process-Constructivist, aiming to select, identify and analyze literature characteristics. The paper selects a set of 25 articles with scientific recognition, that identified the following results: Spain is the country with the highest representativeness of studies developed; University of the Balearic Islands is the most found authors’ home university; Azilah Kasim is prominent author in the area; hotels with more than three stars are the most studied; water consumption in guest rooms are the most analyzed hotels areas; stakeholders’ involvement is essential to an efficient water management, especially manager’s environmental awareness. Aiming to help hotel managers to elaborate a water management plan and review their water usage, water resources management practices in hotels are highlighted, besides the most used indicators. The paper also provides future research opportunities.